STRATEGI PEMASARAN PEDAGANG PASAR TRADISIONAL DALAM PERSPEKTIF EKONOMI ISLAM - Rico, Ricoh Herlambang (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2021)
Very important business in the world of commerce is one of those things very important in human life. Every human being needs assets and wealth to fulfill his needs. The market is a center of economic activity that encourages and facilitates economic activities for the community. The diversity of traders and several factors that underlie both internal and external make the behavior and trading strategies of traders different traders. starting from promoting goods, prices discounts, bonuses, discounts or selling goods at a lower price cheaper. Karangampel Indramayu Traditional Market, is one of the markets in the eastern city of Indramayu. Is a place of trade and service sector activities. This is proven by the existence of a market that is still favored by consumers and middlemen from several areas. strategies carried out by traders on several types of merchandise. Such as giving a discount and bonuses. So that it is feared that it could lead to irregularities trading strategy. Such as elements of fraud (gharar), dishonesty, is prohibited in Islamic law. The research method that the author uses is research qualitative with field the article (field research). In this research consists of data sources, namely primary data sources (data obtained directly from the original source (not through intermediaries) and data sources secondary (research data sources obtained by researchers indirectly directly through intermediaries (obtained and recorded by other parties). For data collection techniques using interviews, documentation, and observation. The final step in the research method is analysis data. With research results: shows that the marketing strategywhat traditional market traders do is mix marketing (marketing mix) consisting of product, price, and promotion. As well as a strategy that is not appropriate is the mixing of goods that are not suitable good quality against ordinary quality without being honest explain the nature or condition of the merchandise.